Kontakty arcybiskupa Nathana Söderbloma (1866-1931) z Kościołami protestanckimi w Niemczech i Polsce - Pirogowicz, Krystyna (My University, 2010)
Praca analizuje kontakty pomiędzy głową protestanckiego Kościoła Szwecji, arcybiskupem Nathanem Söderblomem a przywódcami Kościołów protestanckich w Polsce i Niemczech. W pierwszym rozdziale zanalizowano młodość Söderbloma oraz pokrótce jego poglądy teologiczne, co jest podstawą do zrozumienia jego oryginalnej wizji protestanckiego ekumenizmu. W drugim rozdziale omówiono kontakty Szweda z polskim i niemieckim Kościołem podczas I wojny światowej. Dotyczyły one przede wszystkim prób włączenia przedstawicieli kościelnych w inicjowane przez Söderbloma akcje pokojowe a takŜe organizacji pomocy humanitarnej. Kontakty z polskim Kościołem ograniczyły się do katolickiego arcybiskupa Warszawy, Aleksandra Kakowskiego, oraz urszulanki Julii (Urszuli) Ledóchowskiej. W trzecim rozdziale analizuję politycznoreligijną sytuację w Polsce i Niemczech po 1918 r. W Polsce istniało wtedy siedem odmiennych pod względem narodowościowym i organizacyjnym Kościołów protestanckich a konflikt pomiędzy dwoma największymi zainteresował Söderbloma. Również sytuacja niemieckiego protestantyzmu była złożona, a jego duchowni byli częstokroć zaangażowani politycznie. W czwartym rozdziale przedstawiono konferencję kościelną w Uppsali w 1921 r., która była zwieńczeniem zainteresowań Söderbloma polskim protestantyzmem. Rezolucje uppsalskie były jednak kontrowersyjne i prowadziły do dalszych konflitów. Piąty rozdział omawia kontakty Söderbloma z niemieckim duchownymi po 1921 r. Koncentrowały się one wokół kwestii politycznych – okupacji Zagłębia Ruhry oraz winy za wybuch wojny, a także wokół przygotowań do międzynarodowej konferencji Life and Work planowanej na 1925 r. W rozdziale szóstym analizuję związki Söderbloma z protestantami w Polsce po 1921 r. Ograniczały się one do dwóch przywódców kościelnych, Burschego i Blaua, i dotyczyły głównie dyskusji nad rezolucjami uppsalskimi.

In my Ph. D. thesis I present the contacts between the leader of the Swedish Protestant Church, Nathan Söderblom, and the protestant Church officials from Germany and Poland. In the first chapter I analise the early years of Söderblom’s life and shortly present his theological views as they provide a basis for understanding his model of ecumenism in which religious ideas were connected with his deep interests in social injustice. In the second chapter I present Söderblom’s contacts with the Polish and German Protestant Church during the World War I, which went in two directions: trying to involve the Church leaders in different peace actions and organising the relief work. Söderblom’s contacts with the Polish Protestant Church were limited to the catholic Archbishop of Warsaw, Aleksander Kakowski and ursuline Julia (Urszula) Ledóchowska. In the third chapter I analise the religious and political situation in Poland and Germany after 1918. In Poland Protestantism were torn into religiously and nationally different, separately led units. The conflict between the biggest of them motivated Söderblom to get involved. Even the religious and political situation in Germany was difficult and the German country Churches’ leaders were usually strongly politically involved In the fourth chapter I present the church conference in Uppsala 1921 – the climax of Söderblom’s interests in the Polish. Uppsala resolutions were controversial and satisfied only a part of the protestants. In the fifth chapter I present Söderblom’s contacts with the German Protestant Church after 1921 which were concentrated around two political issues - the occupation of Ruhr by the French army and the question of the German war guilt and, secondly, around the preparations for the international Life and Work conference planned in Stockholm in 1925. In the sixth chapter Söderblom’s contacts with the Polish Protestant Church after 1921 were analised. These were limited to the main Church leaders, Blau and Bursche, and were dominated by renegotiations of the Uppsala conference’s resolutions, and considered also financial help from Sweden.
The contacts between archbishop Natan Söderblom (1866-1931) and the protestant Churches in Germany and Poland
Wydział Historyczny: Instytut Historii
Keywords: Protestantyzm szwedzki, polski, niemiecki; Protestantism in Sweden, Poland and Germany; Kościół; Church; Ruch ekumeniczny; Ecumenical movement